PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN FINANCIAL DISTRESS TERHADAP MANAJEMEN LABA (STUDI KASUS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2014) - DWI A, DAHNIAR (Jurnal Akuntansi AKUNESA, 2015)
Earnings Management is an attempt to intervene in the management of the financial statements related accrual components that can be managed by the manager that is discretionary accrual to realize the desired profitThe purpose of this study to analyze the influence of good corporate governance mechanism, namely institutional ownership, managerial ownership and composition of board of commissioner and the other object is financial distress to earnings management. This research was conducted on Banking companies listed of Indonesian Stock Exchange in 2009-2014.This research is quantitative research and uses linear regression for data analysis. The result of this study shows the corporate governance mechanism (institutional ownership, managerial ownership, composition of board of commissioner not influence to earnings management. Financial distress had positive effect and significant to the earnings management. Keywords: Earnings Management, Institutional Ownership, Managerial Ownership, Composition of Board of Commissioner, Financial Distress